Response characteristics of conducting polypyrrole bi-layer actuators: role of backing layer polymer - Radhakrishnan, S.; Kar, Swarnendu B. (Sensors and Actuators B-Chemical, 2006)
The response of a bi-layer conducting polymer-based actuator has been studied with respect to various parameters such as backing layer thickness, backing layer modulus, applied voltage, etc. The bending angles for the bi-layer actuators made by depositing, conducting polypyrrole (PPy) films on backing layers using LDPE/LLDPE, SBS, Hytrel, PP, PET materials have been compared. The response of the bi-layer actuators indicates that there is optimum for the backing layer thickness as well as its material modulus together with the thickness of the conducting polymer at which the maximum bending is observed. Other geometrical parameters such as a length to width ratio also influence the response of these actuators and have to be chosen properly for the best actuator performance. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: actuator; bi-layer; conducting polymer; polypyrrole; response

Role of dopant ions in electrocatalytic oxidation of methanol using conducting polypyrrole electrodes - Radhakrishnan, S.; Adhikari, Arindam (Journal of Power Sources, 2006)
Conducting polypyrrole electrodes obtained by electro-polymerization of pyrrole on vacuum metallized glass substrates are modified by doping with a range of metal halides as dopant ions having different electronegativity. Electro-oxidation of methanol using these electrodes is studied by means of cyclic voltammetry in 0.1 M HCiO(4) as supporting electrolyte. It is found that the electronegativity of the dopant ion plays a very important role in the electrocatalytic activity. Polypyrrole doped with zirconium chloride gives the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. The results are explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which is associated with the acceptor state created by the dopant in the semi-conducting polymer. (c) 2005 Published by Elsevier B.V.
Keywords: conducting polymers; electrocatalysis; fuel cells; Methanol oxidation; polypyrrole

CO sensor based on polypyrrole functionalized with iron porphyrin - Paul, Santhosh; Amalraj, Francis; Radhakrishnan, S. (Synthetic Metals, 2009)
Polypyrrole (PPy) was chemically functionalized with 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron(III) chloride (FeTPPCl) with special interest on noxious carbon monoxide (CO) gas in ppm level. Controlled functionalization of PPy was achieved with incorporation of various concentrations of porphyrin. The resulted semiconducting material was well characterized by different techniques such as UV-vis spectroscopy, FTIR, GFAAS, XRD, and EDAX. The functionalized polypyrrole material on interdigitated electrode was experienced an immediate increase in resistance when exposed to carbon monoxide gas at very low concentration. The CO gas interacted very fast with the FeTPPCl functionalized PPy at room temperature (RT) and then slowly saturated. The response of these materials was not unidirectional, but reverses to the original resistance level when CO was removed from the test chamber. The highest response factor (Delta R/R(0) x 100) and lowest response time (t(50)) obtained are 12 and 169s, respectively. An optimum level of doping (1 mol% of FeTPPCl) was established for the highest sensitivity and the detection level is as low as 100ppm. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; Fe(III) porphyrin; polypyrrole

Influence of dopant ions on properties of conducting polypyrrole and its electrocatalytic activity towards methanol oxidation - Adhikari, Arindam; Radhakrishnan, S.; Patil, Rahul (Synthetic Metals, 2009)
The polypyrrole (PPy) films were deposited on vacuum metallized substrates by electro-oxidation of pyrrole monomer. These electrodes were then modified with a range of metal halides having different electronegativities. The modified polypyrrole electrodes were employed to investigate electrocatalytic activity towards methanol electrochemical oxidation by means of cyclic voltammetry in 0.1 M HClO(4) as supporting electrolyte. It was found that the electronegativity of the dopant ion incorporated in the PPy film governs the electrocatalytic activity towards methanol oxidation. Among different dopant anions used in the present work, the PPy doped with zirconium chloride gave the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. Electrical property and the charge created due to doping in the polymers were measured using X-ray photoelectron spectroscopy (XPS) and Electron spin resonance spectroscopy (ESR). Electrocatalytic activity of the modified electrodes was correlated with various factors obtained from different polymer characterization experiments. The results were explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: charge transfer; electrocatalyst; ESR; Metal halide dopant; Methanol oxidation; polypyrrole; XPS

Polypyrrole functionalized with FePcTSA for NO(2) sensor application - Paul, Santhosh; Joseph, Michael (Sensors and Actuators B-Chemical, 2009)
The nitrogen dioxide (NO(2)) sensing capability of polypyrrole (PPy) was enhanced dramatically after functionalized with iron(III)phthalocyanine-4,4',4 `',4'''-tetrasulfonic acid monosodium salt (FePcTSA). The incorporated phthalocyanine was confirmed by different characterization techniques such as UV-vis spectroscopy, FTIR, GFAAS, EDAX, etc. The resistance of the functionalized PPy decreased spontaneously during exposure to NO(2) gas at room temperature. This material exhibited excellent stability, reversibility, and reproducibility. The lowest response time (t(50)) thus obtained is 47 s with a highest response factor (Delta R/R(0) x 100) of 50.25. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chemical sensor; Fe(III)phthalocyanine tetrasulfonate; Nitrogen dioxide; polypyrrole

Polypyrrole functionalized with ferrocenyl derivative as a rapid carbon monoxide sensor - Paul, Santhosh; Chavan, Nayaku; Radhakrishnan, S. (Synthetic Metals, 2009)
A rapid carbon monoxide detection system was developed with the electrochemical functioncalization of polypyrrole (PPy) with ferrocenylmethyltrimethylammonium iodide (FTMA-I) as a co-dopant exhibits very high sensitivity to ppm levels of carbon monoxide gas and fast recovery under normal dry room temperature conditions. The co-dopant was synthesized mainly to incorporate into PPy electrochemically to modify the properties in order to sense carbon monoxide (CO) gas. The FTMA-I doped PPy exhibited the characteristics oxidation/reduction peaks for ferrocene in its cyclic voltammograms. The modified PPy films deposited on interdigited electrodes gave rapid sensitivity within a second to 300 ppm carbon monoxide gas and good sensitivity factor was observed even at 4 mmol of the functional groups in the polymer for 300 ppm carbon monoxide gas. This material detected the CO gas concentration as low as 100 ppm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; conducting polymer; polypyrrole

Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction

Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman

Molecularly engineered PW12@Polypyrrole/MXene composite for high-energy, high-rate lithium-ion capacitor - Pawar, Meenakshi D.; Pandey, Priyanshi; Shelke, Manjusha (Journal of Energy Storage, 2026)
Due to inherent differences in the charge storage mechanisms of anode and cathode in a hybrid lithium-ion capacitor (LIC), a significant kinetic balance exists, necessitating the need to improve the ion/electron transfer capability of anode materials. In this study, we have developed a ternary pseudocapacitive composite comprising redox-active phosphotungstic acid nanoclusters (PW12) anchored to polypyrrole nanofibers (PPy), which are further decorated with Ti3C2Tx MXene (PW12@PPy/Ti3C2Tx) synthesized via an in-situ polymerization strategy. Here, Ti3C2Tx MXene serves as a conductive scaffold for PW12 wrapped PPy nanofibers, promoting efficient electron/ion transport. Simultaneously, the incorporation of PW12-anchored PPy nanofibers effectively mitigates the natural tendency of MXene to restack, thus preserving its layered structure. The PW12@PPy/Ti3C2Tx hybrid composite material delivers a high specific capacity of 767 mAh g-1 at 0.1 A g-1 after 100 cycles and a promising cycling stability of 280 mAh g-1 at 1 A g-1 up to 600 cycles. Moreover, an assembled LIC device using PW12@PPy/Ti3C2Tx as anode with nitrogen-doped sucrose carbon (NSC) as cathode demonstrates the highest energy density of 125 Wh kg-1 and maximum power density of 17,058 W kg-1. The device also maintains good cycling stability of 78.4 % capacity retention after 10,000 cycles at 1 A g-1. These results highlight a promising pathway for designing MXene-based hybrid composites with enhanced lithium storage performance, effectively addressing the kinetic mismatch challenges in LIC anode applications.
Keywords: Full cell device; Li ion diffusion; Lithium-ion capacitor; MXene; polyoxometalates; polypyrrole